PELATIHAN PEMBUATAN SABUN DARI MINYAK GORENG BEKAS DI DESA KANGKUNG, KECAMATAN MRANGGEN, KABUPATEN DEMAK - Dwi Handayani Handayani; M. Endy Yulianto; Anggun Puspitarini Siswanto; Heny Kusuma Yanti; Alfiyan Pujiastuti; Rifatul Jannah; Shabrina Berdiansyah (Sekolah Vokasi Universitas Diponegoro, 2020)
The service activity of this Used Soap Cooking Training aims to develop and improve human resources, especially mothers who join the PKK group in the village of Undip Vocational School who collaborate with Kominfo, namely Kangkung Village, Mranggen District, Demak Regency. The development and application of soap making technology from used cooking oil seeks to improve the knowledge and skills of PKK members. The problem solving patterns that will be developed are generally divided into several stages, including: socialization, preparation and training / practice of soap making and monitoring. The training activity which was held to coincide on Mother's Day on December 22, 2019 sought to increase women's empowerment and it was hoped that mothers could obtain provisions in filling their free time after carrying out their duties as housewives to gain knowledge that could support household needs, especially in the family. community environment. With this training, it is expected that mothers are very skilled in utilizing used cooking oil to make soap to meet personal needs and can be developed into a home industry so that it will improve economic problemsThe service activity of this Used Soap Cooking Training aims to develop and improve human resources, especially mothers who join the PKK group in the village of Undip Vocational School who collaborate with Kominfo, namely Kangkung Village, Mranggen District, Demak Regency. The development and application of soap making technology from used cooking oil seeks to improve the knowledge and skills of PKK members. The problem solving patterns that will be developed are generally divided into several stages, including: socialization, preparation and training / practice of soap making and monitoring. The training activity which was held to coincide on Mother's Day on December 22, 2019 sought to increase women's empowerment and it was hoped that mothers could obtain provisions in filling their free time after carrying out their duties as housewives to gain knowledge that could support household needs, especially in the family, community environment. With this training, it is expected that mothers are very skilled in utilizing used cooking oil to make soap to meet personal needs and can be developed into a home industry so that it will improve economic problems.